Guinea-Bissau : First Review Under the Staff Monitored Program. (IMF Staff Country Reports; Country Report, 2021)
After two years of protracted political turmoil and delays in reforms, the authorities put in place in 2021 an ambitious fiscal consolidation program to ensure debt sustainability while creating fiscal space to address vast developmental needs. In late July, a 9-month SMP was approved to support the government's reform program aimed at stabilizing the economy, strengthening governance, and building a sound track-record of policy implementation towards an Extended Credit Facility (ECF) arrangement. Guinea-Bissau is a fragile state with considerable needs to address the COVID-19 pandemic and developmental challenges. A Rapid Credit Facility (RCF) disbursement of SDR 14.2 million (50 percent of quota) was approved in January to provide urgent financing to support critical spending in health and catalyze additional donor resources. The RCF disbursement, the recent SDR 27.2 million allocation (96 percent of quota) and reforms underpinned by the SMP are contributing to address the adverse impact of the pandemic, improve government spending transparency and mitigate debt vulnerabilities, and create conditions that would help restore donor confidence and catalyze much-needed concessional financing.